2009
DOI: 10.1007/s10804-009-9068-9
|View full text |Cite
|
Sign up to set email alerts
|

Parenting Styles and Emotion Regulation: The Role of Behavioral and Psychological Control During Young Adulthood

Abstract: This study examined the relations between maternal parenting styles (including warmth, behavioral control, and psychological control) and young adults' emotion regulation. Participants included 246 young adults from a large Midwestern university, as well as their mothers. Higher levels of maternal control, particularly psychological control, were related to lower levels of young adults' emotion regulation. This study is among the first to explore the above relations within the context of young adulthood. Limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
67
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(76 citation statements)
references
References 32 publications
(36 reference statements)
3
67
0
3
Order By: Relevance
“…Research examining the role of behavioral control (i.e., the use of rewards or punishments to acquire a desired response) and psychological control (i.e., the use of expressed disapproval or guilt by the parent to retain control) during emerging adulthood has found that moderate levels of behavioral control are related to emerging adults' positive emotional and behavioral adjustment [14]. In contrast, high levels of psychological control are related to emerging adults' low self-esteem and social competence as well as high levels of depression, anxiety, and externalizing problems.…”
Section: Disciplinementioning
confidence: 99%
“…Research examining the role of behavioral control (i.e., the use of rewards or punishments to acquire a desired response) and psychological control (i.e., the use of expressed disapproval or guilt by the parent to retain control) during emerging adulthood has found that moderate levels of behavioral control are related to emerging adults' positive emotional and behavioral adjustment [14]. In contrast, high levels of psychological control are related to emerging adults' low self-esteem and social competence as well as high levels of depression, anxiety, and externalizing problems.…”
Section: Disciplinementioning
confidence: 99%
“…Parental psychological control was also related to poorer adolescent selfregulation (Moilanen 2007). Furthermore, because psychological control utilises the emotional relationships between parent and adolescent to control the adolescent, independent emotional regulation may be less likely to develop (Manzeske and Stright 2009;Moilanen 2007). Psychological control is thought to disrupt the development of emotional autonomy by interfering with adolescents' ability to establish and express their own thoughts and feelings and by disturbing the psychoemotional boundary between parents and their adolescents (Barber and Harmon 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Ebeveyn tutumlarının çocukların duygu tanıma becerileri üzerindeki etkilerini konu alan araştırmaları incelediğimizde ise, çocukların duygu tanıma becerilerinin ebeveynlerinin tutumlarıyla ilgili olduğu (Eisenberg, Cumberland ve Spinrad, 1998) ve çocukların gelişimsel sonuçlarıyla en alakalı ebeveyn boyutlarının ise duygusal sıcaklık ve kontrol (reddetme) olduğu görülmüştür (Manzeske, 2009). Bu çalışmaların genelde incelediği ebeveyn ise annedir ve alan yazında mevcut olan ebeveyn tutumları ile ilgili çalışmaların birçoğunda annenin ebeveyn tutumları üzerine yoğunlaşılmıştır.…”
unclassified